For the history of Vyacheslav Ivanov’s translations of Armenian poetry - ALEKSANDROVA, ELMIRA (Bulletin of Yerevan University H: Russian Philology, 2021)
The present study is devoted to the History of creation of Ivanov’s translation of Armenian authors, with the involvement of all the surviving materials: correspondence Bryusov and Ivanov, epistolary materials of others, preparatory materials used poet, manuscripts, translations Ivanov and word for word translation to them from the archival storage of St. Petersburg, Moscow, Rome.